1998
DOI: 10.1177/001789699805700302
|View full text |Cite
|
Sign up to set email alerts
|

Access to healthy foods: part I. Barriers to accessing healthy foods: differentials by gender, social class, income and mode of transport

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link 2 ABSTRACTThis article examines the issues of access to food and the influences people face when shopping for a healthy food basket. It uses data from the Health Education Authority's 1993Health and Lifestyle Survey to examine the barriers people face in accessing a healthy diet.The main findings are that access to food is primarily determined by income, and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 3 publications
3
63
1
2
Order By: Relevance
“…However, there is evidence supporting that in Southern European countries, high education status people tend to consume more fresh fruit and vegetables compared with the low educated (40) . In addition, there is a great deal of literature suggesting that, traditionally, lower socio-economic levels are characterised by unhealthier dietary habits compared with upper socio-economic levels (23,24,41,42) . In addition, several studies in the Mediterranean area have shown that people with low SES had lower adherence to the Mediterranean diet (23)(24)(25)(26) , as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence supporting that in Southern European countries, high education status people tend to consume more fresh fruit and vegetables compared with the low educated (40) . In addition, there is a great deal of literature suggesting that, traditionally, lower socio-economic levels are characterised by unhealthier dietary habits compared with upper socio-economic levels (23,24,41,42) . In addition, several studies in the Mediterranean area have shown that people with low SES had lower adherence to the Mediterranean diet (23)(24)(25)(26) , as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in French working class culture food is important for working capacity and the strength of the body 15 . Also other studies have shown that those on low incomes are more concerned with foods that`fill you up' and provide energy than those that are healthy 63 . Fruits and vegetables are not that filling.…”
Section: ±60mentioning
confidence: 99%
“…Plusieurs études suggè-rent néanmoins que les personnes en situation de précarité possèdent de bonnes aptitudes culinaires [63]. En France [42,64], comme au Royaume-Uni [65] et aux USA [66], ce sont en fait les classes moyennes et aisées qui cuisinent le moins et font le plus appel aux aliments prêts à consommer ou à emporter. Des barrières géographiques entraînent une difficulté d'accès aux commerces proposant une offre alimentaire de qualité à un prix correct.…”
Section: Facteurs Explicatifs Indirectsunclassified
“…Des barrières géographiques entraînent une difficulté d'accès aux commerces proposant une offre alimentaire de qualité à un prix correct. Pour des raisons de stratégie budgétaire et à cause de problèmes de transport, les familles pauvres diversifient leurs lieux d'achats, et fré-quentent plus souvent que les autres les petits commerçants [39,65]. Plusieurs études suggè-rent ainsi que l'accès à une nourriture de bonne qualité est plus difficile dans les quartiers défa-vorisés, parfois qualifiés de « déserts alimentaires » [67].…”
Section: Facteurs Explicatifs Indirectsunclassified